Neuroelectrophysiological Characteristics of the Attention Network in Children with Obstructive Sleep Apnea Accompanied by ADHD-Like Symptoms - Yunxiao Wu; Changming Wang; Dandi Ma; Zhifei Xu; Xiao-lin Ning (Clinical EEG and Neuroscience, 2026)
Objective To investigate the neuroelectrophysiological characteristics of children with obstructive sleep apnea (OSA) accompanied by attention deficit hyperactivity disorder (ADHD)-like symptoms using attention network test (ANT) task-state electroencephalography analysis. Methods All participants completed the Attention Deficit Hyperactivity Disorder rating scale. Electroencephalography data were collected using 32 leads while the participants performed the ANT, followed by polysomnography. Results Of the 87 children, 21 were in the control group, 56 were in the OSA group, and 10 were in the OSA accompanied by ADHD-like symptoms group (OSA-co-ADHD). Each group had similar response time and accuracy for the different ANT conditions. At the O 2 electrode, compared with the controls, the latency of the P1 component in the OSA group was shorter ( P < 0.05). During the alerting network stage, in the P Z electrode, the beta band energy of the OSA-co-ADHD group was greater than that of the control group (Z −3.067, P = 0.006). During the executive control network stage, at the C Z electrode, the OSA-co-ADHD group exhibited higher alpha band energy than the OSA group ( P < 0.05). During the alerting and orienting network phases, the connections of multiple brain regions changed (all P < 0.05), while the executive control network remained unchanged. Conclusion Excessive activation of the alerting network, reorganization of the orienting network in the brain, and compensation for inhibitory control during the process of the executive control network may be important characteristics of children with OSA accompanied by ADHD-like symptoms.